A comparative analysis between the economies of Greece and Ireland - George N. Magoulios; George Exarcho (SPOUDAI - Journal of Economics and Business, 2011)
This paper aims to compare the economies of two of the EU countries of cohesion - Greece and Ireland - which are countries displaying similar initial macroeconomic and structural characteristics. Greece and Ireland have been included in the EU countries of cohesion because of their low level of development. However, Ireland showed higher growth rates in comparison to Greece. The article examines the factors that contributed to the difference in growth rates between the two countries under study. Amongst the most important factors to the advantage of Ireland are: the higher emphasis that Ireland laid on research and technology, the reforms that Ireland performed in education and training, its developmental strategy to attract foreign investments, its neighborhood with the United Kingdom, as well as the financial transfers of the European Union to Ireland.
Keywords: O57; 330; Comparison; Economies; Greece; Ireland